Closed form models for dwell point locations with turnover-based storage assignment policy. (2018) - Huq, Faizul; Hale, Trevor S.; Lutz, Heather S.; Pujari, Nikhil A.
This study investigates where an idle storage-retrieval device should dwell (locate) to minimise the expected response time of its next transaction for both an automated storage/retrieval system (AS/RS) and an automated storage carousel (ASC). A review of the relevant literature showed that previous attempts to obtain the dwell point location only considered a randomised storage assignment policy. This research proposes that under a myriad of operating conditions, the problem can be formulated as a p -median location problem on a tree network to incorporate the turnover-based storage assignment policy.